2022
DOI: 10.4102/aveh.v81i1.778
|View full text |Cite
|
Sign up to set email alerts
|

Microbial keratitis: Causative organisms, susceptibilities and trends at a tertiary eye hospital in South Africa

Abstract: Background: Microbial keratitis is a sight-threatening disease. Empiric management is based on current regional microbial sensitivity patterns.Aim: This study aimed to describe the demographics and microbial patterns of keratitis at St John Eye Hospital and compare it with data from the same centre 10 years prior.Setting: A tertiary eye care centre in Soweto, South Africa.Methods: A retrospective cross-sectional study of the microbiological reports of patients treated for microbial keratitis between 01 January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Microbial keratitis can progress rapidly and lead to ulcers, holes and irreversible vision loss if left untreated. As it can affect vision, it is even more important to act quickly, get the right diagnosis and treat it properly to protect your vision and avoid longterm health risks [7,8]. Although diagnosis and treatment have improved, microbial keratitis still causes visual impairment and blindness worldwide [9,5].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial keratitis can progress rapidly and lead to ulcers, holes and irreversible vision loss if left untreated. As it can affect vision, it is even more important to act quickly, get the right diagnosis and treat it properly to protect your vision and avoid longterm health risks [7,8]. Although diagnosis and treatment have improved, microbial keratitis still causes visual impairment and blindness worldwide [9,5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from several other African countries have shown a diverse aetiology associated with MK from viral causes such as herpes simplex virus type 1 (HSV-1) to a variety of fungal and bacterial species. [7][8][9][10][11][12] There is, therefore, a need for data to enable the development…”
Section: Introductionmentioning
confidence: 99%